BUSINESS STRATEGIES THROUGH FIT MANAGEMENT OF HUMAN CAPITAL AS COMPETITIVE ADVANTAGE - Sihombing, Haeryip; Saptari, Adi; bin Yaakob, Mohd Yuhazri (Journal of Indonesian Economy and Business, 2010)
Many organizations fail to interpret what the competitive advantages of their business.Â Based on lean philosophy about waste, one of the reasons is to unlock (by understandingand take advantages) of their employeeâs potential. This paper proposes a conceptualÂ framework of the so-called âFitted Managementâ. The concept discusses two issues i.e. 1)âFitted Managementâ, an integrated concept of performance challenges, performanceÂ measurement and performance management combined with the vision and missions intocompetitive management; 2) âHuman Transformationâ, a conceptual model to support theÂ first concept. It discusses the processing of exploring human capabilities (in organization)and how to manage this (to fit with the organization) as well as business competition inÂ dynamic market and business climates.Keywords: human capital, competitive advantage, lean, performances, fitted management.